Differences Characteristics of Partial Bowel Obstruction and Total Bowel Obstruction in Ileus Patients at Dr. Soegiri Lamongan Hospital - Nisa, Syeila Ainun; Finansah, Yohni Wahyu; Marlina, Uning; Rochman, Syaiful (Universitas Muhammadiyah Semarang, 2021)
Background: Across all age ranges, one in a thousand people is diagnosed with ileus annually. Ileus is categorized into two types, obstructive ileus, and paralytic ileus. Obstructive ileus is a condition where intestinal passage disorder occurs as a result of a mechanical blockage. There are 7,024 obstructive ileus without hernia in Indonesia and 7,059 paralytic ileus cases in 2004.Objective: To understand the comparison of characteristics of obstructive ileus patients.Method: This analytic descriptive research use the cross-sectional method. Samples are diagnosed with ileus based on the laparotomy result from RSUD Dr. Soegiri, Lamongan. The sampling method is total sampling based on 2015-2019 data. The samples were also using secondary data from medical records, from December 2019 to January 2020.Result: Respondents are mostly male with ages 65 years and over, less than ten days treatment duration, 39 minutes in the average length of partial bowel obstruction surgery duration, 42 minutes in the average length of total bowel obstruction surgery duration, less than two days treatment duration before surgery, percentage of ICU admission as high as 51.5 %, and blood transfusion percentage on 6.1%. There are significant differences in the characteristics of ileus patient’s age (p-value 0,021).Conclusion: Based on this study, it can be concluded that there are differences based on age in the characteristics of partial bowel obstruction and total bowel obstruction on ileus patients, whereas gender, treatment duration, treatment duration before surgery, and surgery duration did not deliver any differences.